WEB-BASED DECISION SUPPORT SYSTEM FOR DIRECT CASH ASSISTANCE (BLT) SELECTION IN KALASEY SATU VILLAGE USING PROFILE - Hendrik, Frieni Tesalonika; Benny Pinontoan; Ketaren, Eliasta (STMIK TIME, 2025)
Direct Cash Assistance (BLT) is a government program to help underprivileged people. The selection process of BLT recipients in Kalasey Satu Village is still manual, which takes a long time and has a high risk of errors. This study aims to implement a web-based Decision Support System using the Profile Matching method to assist the village government in selecting 56 recipients from 120 candidates. The system was developed with the waterfall model using PHP and MySQL, with selection criteria including economic, family, and social aspects. The results showed that candidate A87 obtained the highest score of 4.5245833, and A83 the lowest at 2.0941666. The system was tested using black box testing and functioned properly. This system is expected to help the village government determine BLT recipients.